Technetium-99m stannous pyrophosphate scintigraphy in patients with calcification within the cardiac silhouette. - Wald, R W (1978)
Technetium-99m stannous pyrophosphate scintiscanning was performed in 22 patients with radiographically detected calcification within the cardiac silhouette. All but one of these scintigrams showed a localised area of increased activity similar to that ordinarily seen in acute myocardial infarction. Scintiscans in 3 patients after removal of the calcified aortic valve reverted to negative. It was concluded that this technique for acute infarct detection may yield false positive results in the presence of cardiac calcification.